Uslūb Al-Insyā’ Syair Al-Habīb ‘Idrūs Bin Sālim Al-Jufri Tentang Ilmu (Studi Analisis Balagah) - Aswady, Aji Saputra (Universitas Muhammadiyah Gorontalo, 2023)
This research discusses Uslu>b al-Insya>' in the poem Habi>b 'Idrus about science with the sub-subject matter discussed is how is the conceptof Insya>' al-talabi> contained in the poem Habi>b 'Idru>s about science. Answering the subject matter mentioned above, this research uses several methods, this type of research can be categorized as descriptive qualitative research. As for the source of this research in the book Al-Kaukab Ad-Durri Fi Mana>qib wa Maa>s|ir As-Sayyid Al-Habi>b 'Idru>s bin Sa>lim Al-Jufri (Cet: I, Jakarta: Da>r al-Kutub al-Islamiyah, 2018). The approach used is a multidisciplinary approach. Data collection is carried out with direct quotations and indirect quotations. And data analysis is to analyze Analyzing the concept of forms or variations of Insya>' al-talabi > contained in the poem of the primacy of science with the knife of balagah science analysis. The results showed that the concept of Insha>' al-talabi> contained in Habi>b 'Idru>s poem about science as many as 29 forms of amar, as many as 6 forms of nahy>, as many as 5 forms of istifha>m, as many as 12 forms of nida>' and 2 form of tamanni.